SeqEyes : An Open‐Source Toolbox for Synchronized Waveform/Trajectory Visualization in Pulseq - Xingwang Yong; Zheng Liu; Yiyun Dong; Haotian Hong; Yuting Chen; Paul Dubovan; Qiang Liu; Jiye Kim; Unay Dorken Gallastegi; Yohan Jun; Berkin Bilgic (Magnetic Resonance in Medicine, 2026)
ABSTRACT Pulseq enables vendor‐neutral description of MRI pulse sequences in human‐readable .seq files and is widely used for sequence development and sharing. During design and debugging, rapid evaluation of sequence timing across RF pulses, gradient waveforms, and ADC events is essential. This is particularly challenging for non‐Cartesian acquisitions, where waveform timing does not readily reveal the underlying k ‐space trajectory. Existing tools, however, provide limited interactive capabilities for this task. Here, we introduce SeqEyes, an interactive viewer for Pulseq .seq files tailored for efficient sequence analysis. The software parses .seq files to provide synchronized visualization of RF, gradient, and ADC waveforms alongside their corresponding k ‐space trajectories. This establishes a direct link between sequence structure and sampling behavior within a single interface. The tool supports interactive navigation across time, TRs, and sequence blocks, as well as event‐level timing verification, visualization of Pulseq extensions, and diagnostic overlays. SeqEyes features a graphical user interface, complemented by command‐line, Python, and MATLAB interfaces for integration into existing research workflows. By unifying waveform and trajectory visualizations, this open‐source toolbox optimizes the routine validation of Pulseq sequences, ultimately reducing the barrier to developing and sharing complex MRI acquisitions.